SPECIAL INDUSTRY REPORT SICK BUILDING SYNDROME - CHACE,R; FINE,LJ; MENDELL,MJ (Tufts Archival Research Center, 2007)
Indoor Air Quality Publications report on sick building syndrome (SBS). Includes articles on recent events pertaining to SBS. Details legislation and court hearings on SBS in public areas, transportation, schools, federal buildings, and health facilities. Discusses medical research on the effect of poor indoor air and research into SBS remedies.